Enhancing unreinforced masonry wall resilience through nano-silica modified steel fiber reinforced mortar: A study on in-plane cyclic loading - Ahmed A. Sadoon; Madyan A. Al-Shugaa; Muhammad K. Rahman; Amin Al-Fakih; Mohammed A. Al-Osta (Case Studies in Construction Materials, 2023)
Strengthening existing unreinforced masonry (URM) structures with plaster is a common technique used to improve the structural integrity and durability of buildings. However, using a thin layer of plaster alone may not provide sufficient reinforcement to adequately enhance the URM wall’s resistance to lateral or other types of loading. Therefore, incorporating additional materials, such as steel fibers and nano-silica, into the plaster mix has been explored in this study to further improve the URM wall’s resilience performance. The effect of nano-silica modified steel fibers reinforced (NS-SFR) mortar plastering on the axial and lateral load capacity of concrete masonry walls was experimentally investigated. The investigated URM walls were constructed with a dimension of 830 × 810 × 100 mm (length × width × thickness) using hollow concrete masonry blocks. These walls were categorized as a reference wall, plastered on one side only wall, and plastered on both sides wall. During the experimental testing, each sample was exposed to a combination of precompression and cyclic in-plane loading to assess its shear capacity. The tests also involved closely observing and identifying any cracks or types of failures that occurred. The results of the tests indicated that the walls that were strengthened with NS-SFR mortar exhibited a significant improvement in their compressive strength, shear strength capacity, and stiffness, in comparison to the walls that were not strengthened. Applying NS-SFR mortar as a plaster on the URM wall resulted in significant improvements in both compressive strength and shear capacity. Specifically, for the one-side plastered wall, the use of NS-SFR mortar increased compressive strength and shear capacity by 18.5 % and 40 %, respectively, while for the two sides plastered wall, the increase was even more significant, with improvements of 86.5 % and 132 % in compressive strength and shear capacity, respectively.